The SAGE handbook of African American education - Tillman, Linda C.; Sage eBooks (Los Angeles, [Calif.] ; London : SAGE, 2009)
This handbook reflects historical and current perspectives on African Americans in secondary and post-secondary education. Its content promotes enquiry and development of questions, ideas and dialogues about critical practice, theory and research about African Americans in the US education system.
Specialized.
Description based on print version record.
Includes bibliographical references and index.
Keywords: African American teachers -- Handbooks, manuals, etc; African Americans -- Education -- Handbooks, manuals, etc; Electronic books